Rubber composition for tires and tires

JP7639277B2Active Publication Date: 2025-03-05SUMITOMO RUBBER INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020123066
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-17
Publication Date
2025-03-05
Estimated Expiration
2040-07-17

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、膨潤圧縮法により求められるモノスルフィド結合の架橋密度(νM)及び全架橋密度(νT)が前記式(1)を満たし、シリカを含む充填材と、シランカップリング剤とを含み、前記シランカップリング剤は、アルコキシシリル基及び硫黄原子を含み、かつアルコキシシリル基及び硫黄原子を連結する炭素原子の数が6個以上である有機珪素化合物を含むタイヤ用ゴム組成物であるので、高温でのウェット路面における操縦安定性を向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639277000001
    Figure 0007639277000001
  • Figure 0007639277000002
    Figure 0007639277000002
  • Figure 0007639277000003
    Figure 0007639277000003
Patent Text Reader

Abstract

To provide a tire rubber composition that achieves improved steering stability on a wet road surface at high temperatures and provide a tire.SOLUTION: In a tire rubber composition, a crosslinking density (νM) and a total crosslinking density (νT) of monosulfide bonds, determined by the swelling compressive method, satisfies the formula (1). The tire rubber composition contains a filler including silica, and a silane coupling agent. The silane coupling agent contains an organic silicon compound including alkoxysilyl groups and sulfur atoms, where, carbon atoms connecting the alkoxysilyl groups and sulfur atoms are 6 or more in number. (1)νM / νT≥0.20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition for a tire and a tire. [Background technology]

[0002] Automobile tires are required to have various performances such as wet grip performance, and for example, Patent Document 1 proposes a technique for improving wet steering stability by blending silica, a silane coupling agent, a liquid resin, etc. However, in recent years, from the viewpoint of safety, etc., it is desired to improve steering stability, particularly on wet road surfaces at high temperatures. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-186567 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to solve the above problems and to provide a rubber composition for tires and a tire which improves steering stability on wet road surfaces at high temperatures. [Means for solving the problem]

[0005] The present invention relates to a rubber composition for tires, which has a crosslink density (νM) of a monosulfide bond and a total crosslink density (νT) determined by a swelling compression method that satisfy the following formula (1), and which contains a filler containing silica and a silane coupling agent, wherein the silane coupling agent contains an alkoxysilyl group and a sulfur atom, and the number of carbon atoms connecting the alkoxysilyl group and the sulfur atom is 6 or more. (1)νM / νT≧0.20

[0006] It is preferable that the following formula is satisfied. νM / νT≧0.25

[0007] It is preferable that the following formula is satisfied. νM / νT≧0.30

[0008] It is preferable that the following formula is satisfied. νM≧1.0×10 -5 mol / cm 3

[0009] It is preferable that the content of the filler is 5 to 200 parts by mass per 100 parts by mass of the rubber component, and the content of the organosilicon compound is 0.1 to 20 parts by mass per 100 parts by mass of silica.

[0010] The silica content in 100% by mass of the filler is preferably 30% by mass or more.

[0011] The content of the styrene-butadiene rubber in 100% by mass of the rubber component is preferably 30% by mass or more.

[0012] It is preferable that the content of the styrene-butadiene rubber is 50 to 90 mass % and the content of the butadiene rubber is 10 to 40 mass % in 100 mass % of the rubber component.

[0013] The content of the dialkyldithiophosphate compound per 100 parts by mass of the rubber component is preferably 0.1 to 10 parts by mass.

[0014] The amount of sulfur per 100 parts by mass of the rubber component is preferably 5.0 parts by mass or less.

[0015] The amount of sulfur per 100 parts by mass of the rubber component is preferably 1.0 part by mass or less.

[0016] The content of the plasticizer per 100 parts by mass of the rubber component is preferably 5 to 30 parts by mass.

[0017] It is preferable that the contents of silica and plasticizer per 100 parts by mass of the rubber component satisfy the following formula. 2.4≦Silica content / plasticizer content≦4.0

[0018] It is preferable that the contents of silica and resin per 100 parts by mass of the rubber component satisfy the following formula. 10≦Silica content / Resin content≦20

[0019] The present invention also relates to a tire using the above rubber composition in the tread. Effect of the Invention

[0020] According to the present invention, the rubber composition for tires has a crosslink density (νM) of monosulfide bonds and a total crosslink density (νT) determined by a swelling compression method that satisfy the formula (1), and contains a filler containing silica and a silane coupling agent, and the silane coupling agent contains an organosilicon compound that contains an alkoxysilyl group and a sulfur atom and has 6 or more carbon atoms connecting the alkoxysilyl group and the sulfur atom, and therefore the steering stability on wet road surfaces at high temperatures can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention is a rubber composition for tires, the crosslink density (νM) of the monosulfide bond and the total crosslink density (νT) determined by the swelling compression method satisfy the formula (1), the rubber composition contains a filler containing silica, and a silane coupling agent, the silane coupling agent contains an alkoxysilyl group and a sulfur atom, and the number of carbon atoms connecting the alkoxysilyl group and the sulfur atom is 6 or more. The rubber composition has excellent steering stability on wet road surfaces at high temperatures. That is, when the tire (tread, etc.) becomes hot, the effect of obtaining good steering stability on wet road surfaces is achieved. For example, the effect can be obtained in any case where the tire (tread, etc.) becomes hot, such as when the tire becomes hot directly due to high air temperature, when the road surface becomes hot due to high air temperature, and when the tire becomes hot as a result of high air temperature, and when the tire becomes hot due to high-speed driving regardless of the air temperature.

[0022] The reason why the above-mentioned effects are obtained is not entirely clear, but it is presumed that they are due to the following mechanism. By using an organic silicon compound containing an alkoxysilyl group and a sulfur atom and having 6 or more carbon atoms connecting the alkoxysilyl group and the sulfur atom, i.e., a long-chain silane coupling agent, as a silane coupling agent, the dispersion of silica is promoted, so that the distance between the polymers in the rubber phase becomes uniform. Furthermore, by increasing the "crosslink density (νM) / total crosslink density (νT)≧0.20 of the monosulfide bond", i.e., the relatively short mono-crosslink ratio, the silica interface becomes flexible, and it is possible to obtain a followability to a small deformation and a sufficient heat generation property. In addition, since the mono-crosslink is strong against heat, even if heat is generated by continuous driving, there is little change, and it is possible to prevent a decrease in the stress of the entire rubber. Therefore, it is presumed that the steering stability on wet roads at high temperatures is significantly improved.

[0023] The rubber composition (rubber composition after vulcanization) has a crosslink density of monosulfide bonds (νM (mol / cm 3 )) and total crosslink density (νT (mol / cm 3 )) satisfies the following formula (1). (1)νM / νT≧0.20 From the viewpoint of steering stability on wet road surfaces at high temperatures, vM / vT is preferably 0.25 or more, more preferably 0.30 or more, and even more preferably 0.33 or more. There is no particular upper limit, but vM / vT is preferably 0.50 or less, more preferably 0.45 or less, even more preferably 0.43 or less, and particularly preferably 0.41 or less.

[0024] From the viewpoint of driving stability on wet road surfaces at high temperatures, the rubber composition (rubber composition after vulcanization) has a crosslink density of monosulfide bonds (νM (mol / cm)) determined by a swelling and compression method. 3 )) preferably satisfies the following formula: νM≧1.0×10 -5 mol / cm 3 νM is 1.2×10 -5 mol / cm 3 More than 1.3×10 is preferable. -5 mol / cm 3 More preferably, 1.4×10 -5 mol / cm 3 More preferably, 1.5×10 -5 mol / cm 3 More preferably, the upper limit is 3.5×10 -5 mol / cm 3 Less than 3.0×10 is preferable. -5 mol / cm 3 Less than or equal to 2.8×10 is preferable. -5 mol / cm 3 The following is even more preferred:

[0025] The rubber composition (rubber composition after vulcanization) has a total crosslink density (νT(mol / cm)) determined by a swelling and compression method from the viewpoint of driving stability on wet road surfaces at high temperatures. 3 )) preferably satisfies the following formula: νT≧4.0×10 -5 mol / cm 3 νT is 4.4×10 -5 mol / cm 3 More than 4.7×10 is preferable. -5 mol / cm 3 More than 4.9×10 is preferable. -5 mol / cm 3 More preferably, 5.0×10 -5 mol / cm 3 More preferably, the upper limit is 8.0×10 -5 mol / cm 3 Less than 7.0×10 is preferable. -5 mol / cm 3 Less than 6.5×10 is more preferable. -5 mol / cm 3 The following are particularly preferred:

[0026] In the rubber composition (rubber composition after vulcanization), the crosslink density of the monosulfide bond and the total crosslink density can be determined by the swelling compression method described by Hideo Nakauchi and 4 others in "Japan Rubber Association Journal," Vol. 60, No. 5, pp. 267-272, 1987, in which crosslinks are selectively cut with a reagent such as LiAlH4 or propane 2-thiol, and the crosslink density of the monosulfide bond (R-S1-R) and the total crosslink density are calculated from the swelling degree before and after the selective cutting using the Flory-Rehner formula. Specifically, they can be measured by the method described in the examples below.

[0027] The νM and νT of the rubber composition (rubber composition after vulcanization) can be adjusted by adjusting the amount of sulfur, adjusting the amount of vulcanization accelerator, blending a dialkyldithiophosphate compound, blending the organosilicon compound, etc. Specifically, the value of νM tends to increase by blending a dialkyldithiophosphate compound, blending the organosilicon compound, increasing the ratio of the accelerator to the amount of sulfur, etc. The value of νT tends to increase by increasing the amount of sulfur, increasing the amount of the vulcanization accelerator, etc.

[0028] (Rubber component) As the rubber component usable in the rubber composition, for example, diene rubber can be used. Examples of diene rubber include isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR). Examples of butyl rubber and fluororubber are also included. These may be used alone or in combination of two or more. Among them, from the viewpoint of steering stability on wet road surfaces at high temperatures, SBR, BR, and isoprene rubber are preferred, and SBR and BR are more preferred.

[0029] The diene rubber may be a non-modified diene rubber or a modified diene rubber. The modified diene rubber may be any diene rubber having a functional group that interacts with a filler such as silica. Examples of the modified diene rubber include terminal-modified diene rubber (terminal-modified diene rubber having the functional group at the terminal) in which at least one terminal of the diene rubber has been modified with a compound (modifier) ​​having the functional group, main-chain modified diene rubber having the functional group in the main chain, main-chain terminal-modified diene rubber having the functional group in the main chain and at least one terminal (for example, main-chain terminal-modified diene rubber having the functional group in the main chain and at least one terminal modified with the modifier), and terminal-modified diene rubber modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or epoxy group introduced therein.

[0030] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.

[0031] The SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. These may be used alone or in combination of two or more kinds.

[0032] The styrene content of SBR is preferably 5.0% by mass or more, more preferably 8.0% by mass or more, and even more preferably 10.0% by mass or more. The styrene content is preferably 50.0% by mass or less, more preferably 35.0% by mass or less, even more preferably 30.0% by mass or less, particularly preferably 28.0% by mass or less, and most preferably 27.0% by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved. In this specification, the styrene content is 1 It can be measured by H-NMR measurement.

[0033] The vinyl bond content of SBR is preferably 15% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and most preferably 50% by mass or more. The vinyl bond content is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 65% ​​by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved. In this specification, the vinyl bond amount (1,2-bonded butadiene unit amount) can be measured by infrared absorption spectroscopy.

[0034] The SBR may be unmodified or modified. Modified SBR includes modified SBR into which functional groups similar to those of modified diene rubbers have been introduced. Hydrogenated styrene-butadiene copolymers (hydrogenated SBR) can also be used as SBR.

[0035] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.

[0036] The content of SBR in 100% by mass of the rubber component is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0037] The BR is not particularly limited, and for example, high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These may be used alone or in combination of two or more. In particular, the BR preferably contains high cis BR with a cis content of 90% by mass or more. The cis content is more preferably 95% by mass or more. The cis content can be measured by infrared absorption spectroscopy.

[0038] The BR may be unmodified or modified. The modified BR may be modified BR having the same functional group as the modified diene rubber. The BR may be a hydrogenated butadiene polymer (hydrogenated BR).

[0039] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.

[0040] The BR content in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The upper limit is preferably 60% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0041] Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, and modified IR. Examples of NR include SIR20, RSS♯3, TSR20, and other rubber industry-standard rubbers. Examples of IR include IR2200 and other rubber industry-standard rubbers. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), and other rubbers. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. Examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These may be used alone or in combination of two or more.

[0042] When the rubber composition contains an isoprene-based rubber, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. By keeping the content within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0043] (silica) Silica is compounded as a filler in the rubber composition. Usable silica includes dry process silica (anhydrous silica) and wet process silica (hydrated silica). Among them, wet process silica is preferred because it has a large number of silanol groups. Commercially available products include those from Degussa, Rhodia, Tosoh Silica, Solvay Japan, and Tokuyama. These may be used alone or in combination of two or more.

[0044] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 100m 2 / g or more, more preferably 150m 2 The upper limit of the N2SA of silica is not particularly limited, but is preferably 250 m 2 / g or less, more preferably 220m 2 / g or less, more preferably 200m 2 By keeping the value within the above range, there is a tendency for high-speed cornering performance on wet road surfaces to improve. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-93.

[0045] In the rubber composition, the content of silica is preferably 5 parts by mass or more, more preferably 50 parts by mass or more, even more preferably 60 parts by mass or more, and particularly preferably 70 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 120 parts by mass or less, and particularly preferably 100 parts by mass or less. By keeping the content within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0046] (Silane coupling agent) The silane coupling agent used in the rubber composition contains an organosilicon compound that contains an alkoxysilyl group and a sulfur atom, and the number of carbon atoms connecting the alkoxysilyl group and the sulfur atom is 6 or more. Such organosilicon compounds may be used alone or in combination of two or more. Among the organosilicon compounds, an organosilicon compound represented by the following average composition formula (I) is preferred. [ka] (In the formula, x represents the average number of sulfur atoms and is 3.5 or more. m represents an integer of 6 or more. 1 ~R 6 are the same or different and each represents an alkyl group or an alkoxy group having 1 to 6 carbon atoms; R 1 ~R 3 At least one of and R 4 ~R 6 At least one of R is the alkoxy group. 1 ~R 6 may be a ring structure formed by bonding the alkyl group or the alkoxy group.

[0047] x represents the average number of sulfur atoms in the organosilicon compound, and is preferably 3.5 or more and 12 or less. Here, the average number of sulfur atoms and the number of silicon atoms are values ​​calculated from the molecular weights of the sulfur and silicon atoms in the composition measured by fluorescent X-rays.

[0048] m represents an integer of 6 or more, and preferably 6 or more and 14 or less.

[0049] Alkyl group (R 1 ~R 6 The number of carbon atoms in the alkyl group is preferably 1 to 5. The alkyl group may be linear, branched, or cyclic. Specific examples include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group.

[0050] Alkoxy group (R 1 ~R 6 ) preferably has 1 to 5 carbon atoms. The hydrocarbon group in the alkoxy group may be linear, branched, or cyclic. Specific examples include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, and an n-butoxy group.

[0051] R 1 ~R 3 At least one of and R 4 ~R 6 At least one of R is an alkoxy group having 1 to 6 carbon atoms, and preferably R 1 ~R 3 , R 4 ~R 6 At least two of each of these are alkoxy groups having 1 to 6 carbon atoms.

[0052] In addition, R 1 ~R 6 may be a ring structure formed by bonding an alkyl group or an alkoxy group having 1 to 6 carbon atoms. For example, (i) R 1 is an ethoxy group, R 2 (ii) R 1 is an ethyl group, R2 When R forms a ring structure with a methyl group bonded thereto, 1 and R 2 Examples of structures in which divalent groups such as "-O-C2H4-CH2-" and "-C2H4-CH2-" are formed and bonded to Si include

[0053] The organosilicon compound can be prepared, for example, by the manufacturing method described in JP 2018-65954 A. Specifically, the organosilicon compound can be produced by reacting a halogen-containing organosilicon compound of formula (I-1) described in JP 2018-65954 A, anhydrous sodium sulfide represented by Na2S, and sulfur as necessary. When carrying out the above reaction, the addition of sulfur is optional for adjusting the sulfide chain, and may be determined from the blending amount of the compound of the average composition formula (I-1), anhydrous sodium sulfide, and sulfur as necessary, so as to obtain a compound of the desired average composition formula (I). For example, if you want to make the x of the compound of the average composition formula (I) 3.5, you can react 1.0 mol of anhydrous sodium sulfide, 2.5 mol of sulfur, and 2.0 mol of the compound of formula (I-1).

[0054] And, when an organic silicon compound containing an alkoxysilyl group and a sulfur atom and having 6 or more carbon atoms connecting the alkoxysilyl group and the sulfur atom is used as a silane coupling agent, that is, a long-chain silane coupling agent, the alkoxy group in the compound reacts with the hydroxyl group on the silica surface to hydrophobize the silica surface, and the effect of hydrophobization is greater than that of conventional silane coupling agents due to the long carbon chain of the compound, so that the dispersibility of silica is significantly improved. In addition, the uniform dispersion of silica due to the long chain structure also makes it possible to make the distance between polymers in the rubber phase uniform. Furthermore, as mentioned above, the relatively short mono-crosslinking ratio is high, so that it is possible to obtain a followability with a small deformation and a sufficient heat generation property, and further, even if heat is generated by continuous driving, there is little change, and the stress of the entire rubber can be prevented from decreasing. Therefore, by using such a long-chain silane coupling agent, the steering stability on wet roads at high temperatures can be significantly improved.

[0055] In the rubber composition, the content of the organosilicon compound is preferably 0.1 parts by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of silica. The upper limit of the content is preferably 50 parts by mass, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved. The content of the organosilicon compound represented by the average composition formula (I) is also preferably within the same range.

[0056] The rubber composition may contain a silane coupling agent other than the organosilicon compound that contains an alkoxysilyl group and a sulfur atom and in which the number of carbon atoms connecting the alkoxysilyl group and the sulfur atom is 6 or more. The other silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamate, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide ...3-trimethoxysilylpropyl-N,N-dimethylthiocarbamate, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(2-trimethoxysilylpropyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysil Examples of such silanes include sulfide-based silanes such as rubamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and Momentive's NXT and NXT-Z; vinyl-based silanes such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based silanes such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silanes such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Commercially available products include those manufactured by Degussa, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.

[0057] In the rubber composition, the content of the silane coupling agent (the total amount of the organic silicon compound and other silane coupling agents) is preferably 0.1 parts by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of silica. The upper limit of the content is preferably 50 parts by mass, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0058] (Other filling materials) The filler other than silica is not particularly limited, and materials known in the rubber field can be used, such as inorganic fillers such as carbon black, calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica. Of these, carbon black and aluminum hydroxide are preferred.

[0059] In the rubber composition, the content of the filler (total content of the fillers) is preferably 5 parts by mass or more, more preferably 55 parts by mass or more, even more preferably 65 parts by mass or more, and particularly preferably 75 parts by mass or more, per 100 parts by mass of the rubber component. The upper limit of the content is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 120 parts by mass or less, and particularly preferably 100 parts by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0060] In the rubber composition, the silica content in 100% by mass of the filler is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more, from the viewpoint of steering stability on wet road surfaces at high temperatures. The upper limit is not particularly limited, but is preferably 98% by mass or less, more preferably 97% by mass or less.

[0061] The carbon black that can be used in the rubber composition is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those manufactured by Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin-Nichika Carbon Co., Ltd., Columbia Carbon Co., Ltd., and the like. These may be used alone or in combination of two or more kinds.

[0062] The nitrogen adsorption specific surface area (N2SA) of carbon black is 50m 2 / g or more is preferable, and 70m 2 / g or more is more preferable, and 90m 2 / g or more is more preferable. 2 / g or less is preferable, and 150m 2 / g or less is more preferable, and 130m 2 By keeping it within the above range, there is a tendency that the driving stability on wet road surfaces at high temperatures is improved. The nitrogen adsorption specific surface area of ​​carbon black can be determined in accordance with JIS K6217-2:2001.

[0063] In the rubber composition, the content of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. By keeping the content within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0064] The aluminum hydroxide is not particularly limited, and any aluminum hydroxide commonly used in the tire industry can be used. These may be used alone or in combination of two or more kinds.

[0065] The average primary particle size of aluminum hydroxide is preferably 0.6 μm or more, more preferably 0.7 μm or more. The average primary particle size of aluminum hydroxide is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 1.3 μm or less, and particularly preferably 1.2 μm or less. Within the above range, the effect tends to be better obtained. In this specification, the average primary particle size of aluminum hydroxide is a number average particle size, which is measured by a transmission electron microscope.

[0066] In the rubber composition, the content of aluminum hydroxide is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less. By keeping the content within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0067] (Plasticizer) The rubber composition may contain a plasticizer. A plasticizer is a material that imparts plasticity to a rubber component, and examples of the plasticizer include liquid plasticizers (plasticizers that are in a liquid state at room temperature (25°C)) and resins (resins that are in a solid state at room temperature (25°C)). Among these, resins are preferred from the viewpoint of steering stability on wet road surfaces at high temperatures.

[0068] In the rubber composition, the content of the plasticizer (the total amount of the liquid plasticizer (a plasticizer in a liquid state at room temperature (25° C.)) and the resin (a resin in a solid state at room temperature (25° C.))) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, per 100 parts by mass of the rubber component. The upper limit of the content is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less. By keeping it within the above range, there is a tendency that the steering stability on wet road surfaces at high temperatures is improved.

[0069] Liquid plasticizers (plasticizers that are liquid at room temperature (25° C.)) that can be used in the rubber composition are not particularly limited, and examples include oils, liquid resins, liquid diene polymers, etc. These may be used alone or in combination of two or more kinds.

[0070] In the rubber composition, the content of the liquid plasticizer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less. By keeping the content within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0071] Examples of the oil include process oil, vegetable oil, or a mixture thereof. Examples of the process oil include paraffin-based process oil, aromatic process oil, and naphthenic process oil. Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. Examples of commercially available products include products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mill Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., and Nisshin Oillio Group Co., Ltd. Among these, process oils (paraffin-based process oils, aromatic process oils, naphthenic process oils, etc.) and vegetable oils are preferred.

[0072] Examples of liquid resins include terpene resins (including terpene phenol resins and aromatic modified terpene resins) that are liquid at 25°C, rosin resins, styrene resins, C5 resins, C9 resins, C5 / C9 resins, dicyclopentadiene (DCPD) resins, coumarone-indene resins (including coumarone and indene simple resins), phenol resins, olefin resins, polyurethane resins, and acrylic resins.

[0073] Examples of liquid diene polymers include liquid styrene butadiene copolymers (liquid SBR), liquid butadiene polymers (liquid BR), liquid isoprene polymers (liquid IR), liquid styrene isoprene copolymers (liquid SIR), liquid styrene butadiene styrene block copolymers (liquid SBS block polymers), liquid styrene isoprene styrene block copolymers (liquid SIS block polymers), liquid farnesene polymers, liquid farnesene butadiene copolymers, etc., which may be modified at the ends or main chains with polar groups.

[0074] Examples of the resins (resins in a solid state at room temperature (25°C)) that can be used in the rubber composition include aromatic vinyl polymers, coumarone-indene resins, coumarone resins, indene resins, phenolic resins, rosin resins, petroleum resins, terpene resins, and acrylic resins that are in a solid state at room temperature (25°C). The resins may be hydrogenated. These may be used alone or in combination of two or more. Of these, aromatic vinyl polymers, coumarone-indene resins, phenolic resins, and petroleum resins are preferred from the viewpoint of steering stability on wet road surfaces at high temperatures.

[0075] In the rubber composition, the content of the resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved. The same range is also suitable for the content of the aromatic vinyl polymer.

[0076] The softening point of the resin is preferably 60° C. or higher, more preferably 70° C. or higher, and even more preferably 80° C. or higher. The upper limit is preferably 160° C. or lower, more preferably 130° C. or lower, and even more preferably 115° C. or lower. By keeping the softening point within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved. The softening point of the resin is the temperature at which the ball drops when the softening point specified in JIS K6220-1:2001 is measured using a ring and ball softening point tester.

[0077] The aromatic vinyl polymer is a polymer containing an aromatic vinyl monomer as a structural unit. For example, it can be a resin obtained by polymerizing α-methylstyrene and / or styrene, and specifically, it can be a homopolymer of styrene (styrene resin), a homopolymer of α-methylstyrene (α-methylstyrene resin), a copolymer of α-methylstyrene and styrene, a copolymer of styrene and another monomer, etc.

[0078] The coumarone-indene resin is a resin containing coumarone and indene as main monomer components constituting the resin skeleton (main chain). Other monomer components contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0079] The coumarone resin is a resin containing coumarone as a main monomer component constituting the skeleton (main chain) of the resin.

[0080] The indene resin is a resin containing indene as a main monomer component constituting the skeleton (main chain) of the resin.

[0081] The phenolic resin may be a known polymer obtained by reacting phenol with an aldehyde such as formaldehyde, acetaldehyde, or furfural in the presence of an acid or alkali catalyst. Among these, those obtained by reacting with an acid catalyst (such as novolac-type phenolic resin) are preferred.

[0082] Examples of the rosin resin include rosin-based resins such as natural rosin, polymerized rosin, modified rosin, ester compounds thereof, and hydrogenated products thereof.

[0083] Examples of the petroleum resin include C5 resin, C9 resin, C5 / C9 resin, dicyclopentadiene (DCPD) resin, etc. Among these, DCPD resin is preferable.

[0084] The terpene resin is a polymer containing terpene as a structural unit. For example, polyterpene resin obtained by polymerizing a terpene compound, aromatic modified terpene resin obtained by polymerizing a terpene compound and an aromatic compound, etc. can be mentioned. Hydrogenated products of these can also be used.

[0085] The polyterpene resin is a resin obtained by polymerizing a terpene compound. The terpene compound is (C5H8) n The hydrocarbons and their oxygen-containing derivatives represented by the composition 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 ), and examples thereof include α-pinene, β-pinene, dipentene, limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, and γ-terpineol.

[0086] Examples of the polyterpene resin include pinene resin, limonene resin, dipentene resin, pinene / limonene resin, etc., which are made from the above-mentioned terpene compounds. Among them, pinene resin is preferable. Pinene resin usually contains both α-pinene and β-pinene, which are isomers, but depending on the components contained, it is classified into β-pinene resin mainly composed of β-pinene and α-pinene resin mainly composed of α-pinene.

[0087] Examples of the aromatic modified terpene resin include terpene phenol resins made from the above terpene compounds and phenolic compounds, and terpene styrene resins made from the above terpene compounds and styrene compounds. Terpene phenol styrene resins made from the above terpene compounds, phenolic compounds, and styrene compounds can also be used. Examples of the phenolic compounds include phenol, bisphenol A, cresol, and xylenol. Examples of the styrene compounds include styrene and α-methylstyrene.

[0088] The acrylic resin is a polymer containing an acrylic monomer as a constituent unit. For example, a styrene-acrylic resin having a carboxyl group and obtained by copolymerizing an aromatic vinyl monomer component and an acrylic monomer component, such as a styrene-acrylic resin, can be used. Among them, a solventless carboxyl group-containing styrene-acrylic resin can be preferably used.

[0089] The solvent-free carboxyl group-containing styrene-acrylic resin is a (meth)acrylic resin (polymer) synthesized by a high-temperature continuous polymerization method (high-temperature continuous bulk polymerization method) (methods described in U.S. Pat. No. 4,414,370, JP-A-59-6207, JP-B-5-58005, JP-A-1-313522, U.S. Pat. No. 5,010,166, Toa Gosei Kenkyuu Nenpo TREND 2000 Vol. 3, p. 42-45, etc.) with minimal use of auxiliary raw materials such as polymerization initiators, chain transfer agents, and organic solvents. In this specification, (meth)acrylic means methacryl and acrylic.

[0090] Examples of the acrylic monomer components constituting the acrylic resin include (meth)acrylic acid, (meth)acrylic acid esters (alkyl esters such as 2-ethylhexyl acrylate, aryl esters, aralkyl esters, etc.), (meth)acrylamide, (meth)acrylic acid derivatives such as (meth)acrylamide derivatives, etc. (Meth)acrylic acid is a general term for acrylic acid and methacrylic acid.

[0091] Examples of the aromatic vinyl monomer component constituting the acrylic resin include aromatic vinyls such as styrene, α-methylstyrene, vinyltoluene, vinylnaphthalene, divinylbenzene, trivinylbenzene, and divinylnaphthalene.

[0092] As the monomer components constituting the acrylic resin, other monomer components may be used in addition to the (meth)acrylic acid, (meth)acrylic acid derivatives, and aromatic vinyl.

[0093] Examples of the plasticizer that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JXTG Nippon Oil & Energy Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.

[0094] From the viewpoint of steering stability on wet road surfaces at high temperatures, it is preferable that the rubber composition has a silica content (parts by mass) per 100 parts by mass of the rubber component and a plasticizer content (parts by mass) per 100 parts by mass of the rubber component that satisfy the following formula: 2.0≦Silica content / plasticizer content≦4.5 The silica content / plasticizer content is preferably 2.4 or more, more preferably 2.6 or more, even more preferably 2.8 or more, and particularly preferably 3.0 or more. The lower limit is preferably 4.0 or less, more preferably 3.8 or less, even more preferably 3.6 or less, and particularly preferably 3.4 or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0095] From the viewpoint of steering stability on wet road surfaces at high temperatures, it is preferable that the rubber composition has a silica content (parts by mass) per 100 parts by mass of the rubber component and a resin content (parts by mass) per 100 parts by mass of the rubber component (a resin in a solid state at room temperature (25° C.)) that satisfies the following formula: 5≦Silica content / Resin content≦25 The silica content / plasticizer content is preferably 10 or more, more preferably 12 or more, even more preferably 14 or more, and particularly preferably 15 or more. The lower limit is preferably 20 or less, more preferably 19 or less, even more preferably 18 or less, and particularly preferably 17 or less. By keeping it within the above range, the steering stability on wet road surfaces at high temperatures tends to be improved.

[0096] From the viewpoint of steering stability on wet road surfaces at high temperatures, the rubber composition preferably contains a dialkyldithiophosphate compound.

[0097] The reason why such an effect is obtained is not entirely clear, but it is presumed that the effect is due to the following mechanism. By introducing a compound such as zinc dithiophosphate, the alkyl group becomes compatible with the rubber, while zinc, accompanied by vulcanizing agents such as sulfur and accelerators, tends to form relatively short mono-crosslinks in the system. By increasing the relatively short mono-crosslink ratio, the silica interface becomes flexible, and it is possible to obtain sufficient heat generation while also obtaining a followability to minute deformation. In addition, since the mono-crosslink is strong against heat, even if heat is generated by continuous driving, there is little change, and it is possible to prevent the stress of the entire rubber from decreasing. Therefore, it is presumed that the use of a dialkyldithiophosphate compound together with the organosilicon compound (long-chain silane coupling agent) significantly improves the steering stability on wet roads at high temperatures.

[0098] As the dialkyldithiophosphate compound, for example, a salt of dialkyldithiophosphate with a metal such as zinc or molybdenum can be used. As a commercially available product, a product from Rhein Chemie can be used. These may be used alone or in combination of two or more. Among them, the compound represented by the following formula (zinc dialkyldithiophosphate) is preferred. [ka] (In the formula, R 1 ~R 4 each independently represents a linear or branched alkyl group having 1 to 18 carbon atoms, or a cycloalkyl group having 5 to 12 carbon atoms.

[0099] In the above formula, R 1 ~R 4 Examples of the linear or branched alkyl group represented by R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a 4-methylpentyl group, a 2-ethylhexyl group, an octyl group, and an octadecyl group, while examples of the cycloalkyl group include a cyclopentyl group, a cyclohexyl group, and a cyclooctyl group. Among these, R 1 ~R 4is preferably a linear or branched alkyl group having 2 to 8 carbon atoms, more preferably an n-butyl group, an n-propyl group, an iso-propyl group, or an n-octyl group, and further preferably an n-butyl group.

[0100] The content of the dialkyldithiophosphate compound is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and particularly preferably 2 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be better obtained. The content of the zinc dialkyldithiophosphate is also preferably within the same range.

[0101] (Other materials) From the viewpoints of crack resistance, ozone resistance, and the like, the rubber composition preferably contains an antioxidant.

[0102] The antiaging agent is not particularly limited, and examples thereof include naphthylamine-based antiaging agents such as phenyl-α-naphthylamine; diphenylamine-based antiaging agents such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, Examples of the antioxidant include p-phenylenediamine antioxidants such as amines; quinoline antioxidants such as polymerized 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Among these, p-phenylenediamine antioxidants and quinoline antioxidants are preferred, and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and polymerized 2,2,4-trimethyl-1,2-dihydroquinoline are more preferred. Commercially available products include, for example, products from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and Flexis Co., Ltd.

[0103] In the rubber composition, the content of the antioxidant is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 7.0 parts by mass or less, more preferably 4.0 parts by mass or less.

[0104] The rubber composition preferably contains stearic acid. The content of stearic acid in the rubber composition is preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the rubber component.

[0105] As the stearic acid, any known stearic acid can be used, for example, products available from NOF Corporation, NOF Corporation, Kao Corporation, Fujifilm Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.

[0106] The rubber composition preferably contains zinc oxide. The content of zinc oxide in the rubber composition is preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the rubber component.

[0107] As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.

[0108] The rubber composition may contain wax. The content of the wax in the rubber composition is preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the rubber component.

[0109] The wax is not particularly limited, and examples thereof include petroleum waxes, natural waxes, etc. Also, synthetic waxes obtained by refining or chemically treating multiple waxes can be used. These waxes may be used alone or in combination of two or more kinds.

[0110] Examples of petroleum waxes include paraffin wax and microcrystalline wax. Examples of natural waxes are not particularly limited as long as they are derived from resources other than petroleum, and include, for example, vegetable waxes such as candelilla wax, carnauba wax, Japan wax, rice wax, and jojoba wax; animal waxes such as beeswax, lanolin, and spermaceti; mineral waxes such as ozokerite, ceresin, and petrolactam; and refined products thereof. Examples of commercially available products include products from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., and Seiko Chemical Co., Ltd.

[0111] It is preferable to compound sulfur in the rubber composition, in order to form an appropriate amount of crosslinked chains in the polymer chains and to impart good performance.

[0112] In the rubber composition, the amount of sulfur is preferably 0.1 part by mass or more, more preferably 0.3 part by mass or more, and even more preferably 0.5 part by mass or more, based on 100 parts by mass of the rubber component. The amount is preferably 5.0 parts by mass or less, more preferably 2.5 parts by mass or less, even more preferably 1.5 parts by mass or less, and particularly preferably 1.0 part by mass or less.

[0113] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0114] The rubber composition preferably contains a vulcanization accelerator. In the rubber composition, the content of the vulcanization accelerator is not particularly limited and may be freely determined according to the desired vulcanization speed and crosslink density, but is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 8.0 parts by mass or less, more preferably 6.0 parts by mass or less, and even more preferably 5.0 parts by mass or less.

[0115] The type of vulcanization accelerator is not particularly limited, and any commonly used accelerator can be used. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenyl guanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide-based, guanidine-based and benzothiazole-based vulcanization accelerators are preferred.

[0116] In addition to the above-mentioned components, the rubber composition may contain compounding agents generally used in the tire industry, such as materials such as a mold release agent, as appropriate.

[0117] The rubber composition can be produced by a known method, for example, by kneading the components using a rubber kneading device such as an open roll or a Banbury mixer, followed by vulcanization.

[0118] As for the kneading conditions, in the base kneading step in which additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 50 to 200°C, preferably 80 to 190°C, and the kneading time is usually 30 seconds to 30 minutes, preferably 1 minute to 30 minutes. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 100°C or lower, preferably room temperature to 80°C. Furthermore, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 120 to 200°C, preferably 140 to 180°C.

[0119] The rubber composition can be preferably used for each component of a pneumatic tire such as a tread (cap tread), a sidewall, a base tread, a bead apex, a clinch apex, an inner liner, an under tread, a breaker topping, a braid topping, a tread, etc. Among them, the rubber composition can be preferably used for a tread (cap tread).

[0120] A tire is manufactured by a conventional method using a rubber composition. That is, the rubber composition containing the above-mentioned components is extruded in an unvulcanized state to match the shape of a tread, etc., and molded together with other tire components in a conventional manner on a tire building machine to form an unvulcanized tire. The unvulcanized tire is heated and pressurized in the vulcanizer to obtain a tire.

[0121] Examples of the tire include pneumatic tires and non-pneumatic tires. Among them, pneumatic tires are preferred. The tire can be used as a passenger car tire, a large passenger car tire and a large SUV tire, a heavy load tire such as a truck and a bus tire, a light truck tire, a two-wheeled vehicle tire, a racing tire (high performance tire), etc. Among them, the tire can be preferably used as a passenger car tire, a large passenger car tire, and a large SUV tire. EXAMPLES

[0122] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0123] Various chemicals used in the examples and comparative examples will be collectively described below. SBR: HPR850 manufactured by JSR Corporation (styrene content: 27.5% by mass, vinyl bond content: 59.0% by mass) BR: Ubepol BR150B (cis content 98% by mass) manufactured by Ube Industries, Ltd. Carbon black: Diablack N220 (N2SA115m) manufactured by Mitsubishi Chemical Corporation 2 / g) Silica: Ultrasil VN3 (N2SA175m) manufactured by Evonik Degussa 2 / g) Organosilicon compound 1: Silane coupling agent synthesized in Production Example 1 below Organosilicon compound 2: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Degussa Oil: Diana Process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Resin: Sylvares 4401 (α-methylstyrene and Copolymer with styrene, softening point 85℃, Tg 43℃) Wax: Ozoace wax made by Nippon Seiro Co., Ltd. Antioxidant 1: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Antioxidant 2: Nocrac RD (poly(2,2,4-trimethyl-1,2-dihydroquinoline)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Stearic acid: NOF Corporation's "Tsubaki" stearic acid Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Co., Ltd. Dialkyldithiophosphate compound: TP-50 (a mixture of zinc dithiophosphate and polymer, R 1 ~R 4 n-Butyl group, active ingredient 50% by weight Vulcanization accelerator: Noccela NS (N-tert-butyl-) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. 2-Benzothiazylsulfenamide (TBBS)

[0124] (Production Example 1: Synthesis of Organosilicon Compound 1) In a 2L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 78.0g (1.0 mol) of anhydrous sodium sulfide, 80.3g (2.5 mol) of sulfur and 480g of ethanol were charged and heated to 80°C. 566g (2.0 mol) of 6-chlorohexyltriethoxysilane was added dropwise therein and heated and stirred at 80°C for 10 hours. The reaction liquid was filtered under pressure using a filter plate to obtain a filtrate from which the salt generated as the reaction proceeded was removed. The obtained filtrate was heated to 100°C, and ethanol was distilled off under a reduced pressure of 10mmHg or less to obtain an organosilicon compound 1 (silane coupling agent) as a reaction product. The obtained organosilicon compound 1 had a sulfur content of 18.5% by mass, the average number of sulfur atoms x contained in one molecule of the organosilicon compound was 3.5, and the value of m was 6.

[0125] <Examples and Comparative Examples> According to the compounding recipes shown in each table, polymers and compounding chemicals were added using a 1.7 L Banbury mixer, and the mixture was kneaded for 3 minutes at 150°C to obtain a kneaded product. Sulfur and a vulcanization accelerator were added, and the mixture was kneaded for 2 minutes at 100°C using an open roll to obtain an unvulcanized rubber composition. Each of the obtained unvulcanized rubber compositions was molded into the shape of a cap tread, laminated together with other tire components, and vulcanized at 170°C for 15 minutes to produce a test tire (tire size: 195 / 65R15).

[0126] The following physical property measurements and evaluations were carried out on the obtained test tires. The evaluation results are shown in the tables. In addition, in Tables 1 and 2, Comparative Examples 1-1 and 2-1 were used as reference comparative examples, respectively.

[0127] [Swelling compression method] A test piece (2 cm x 2 cm, 1 mm thick (rubber composition after vulcanization)) taken from the tread of a test tire was immersed in a solution of tetrahydrofuran and toluene mixed in a 1:1 ratio for one day to swell. The swelling compression of this swollen sample was measured using a thermomechanical analyzer (Shimadzu Corporation, product name "TMA-50"). Then, the total network density (total crosslink density (νT)) (mol / cm) was calculated from the swelling compression of the swollen sample using the Flory-Rehner equation. 3 ) was calculated. In addition, the sample was immersed in a solution saturated with LiAlH4, which was a mixture of tetrahydrofuran and toluene in a 1:1 ratio, for one day to swell. The swelling and compression degree of the swollen sample was measured in the same manner, and the network density was calculated using the Flory-Rehner equation to obtain the network density of monosulfide (crosslink density of monosulfide bonds (νM)) (mol / cm 3 ) was decided.

[0128] <Handling stability on wet roads at high temperatures (actual vehicle)> Test tires were fitted and driven around a test course with a wet road surface under conditions where the tires were at high temperatures (20°C temperature and an average speed of 120 km / h), and the responsiveness during cornering was then evaluated on a 10-point scale from 1 to 10 based on the driver's feeling. The same test was carried out by a total of 10 drivers, and the total score was calculated for each test tire, and indexed so that the total score of the reference comparative example (Comparative Example 1-1 in Table 1, Comparative Example 2-1 in Table 2) was 100. The higher the index, the better the handling stability on wet road surfaces at high temperatures.

[0129] [Table 1]

[0130] [Table 2]

[0131] From each table, it can be seen that the examples which satisfy the above formula (1) "M300 / M100 ≧ 4.0", satisfy the above formula (1) "νM / νT ≧ 0.20", and contain a filler containing silica, and a silane coupling agent containing an organosilicon compound which contains an alkoxysilyl group and a sulfur atom and has 6 or more carbon atoms connecting the alkoxysilyl group and the sulfur atom, had excellent steering stability on wet road surfaces at high temperatures.

Claims

1. The crosslink density (νM) of the monosulfide bond and the total crosslink density (νT) determined by a swelling and compression method satisfy the following formula (1), The composition includes a styrene-butadiene rubber, a resin, a filler including silica, and a silane coupling agent, The styrene butadiene rubber has a styrene content of 5.0 to 30.0 mass%; The silane coupling agent includes an organosilicon compound that contains an alkoxysilyl group and a sulfur atom, and the number of carbon atoms connecting the alkoxysilyl group and the sulfur atom is 6 or more, The rubber composition for tires, wherein the organosilicon compound is an organosilicon compound represented by the following average composition formula (I): (1) νM / νT≧0.20 【Chemistry 1】 (In the formula, x represents the average number of sulfur atoms and is 3.5 or more. m represents an integer of 6 or more. R 1 ~R 6 are the same or different and each represents an alkyl group or an alkoxy group having 1 to 6 carbon atoms; R 1 ~R 3 and R 4 ~R 6 At least one of R is the alkoxy group. 1 ~R 6 may be a ring structure formed by bonding the alkyl group or the alkoxy group.

2. The rubber composition for tires according to claim 1, which satisfies the following formula: νM / νT≧0.25

3. The rubber composition for tires according to claim 1, which satisfies the following formula: νM / νT≧0.30

4. The rubber composition for tires according to any one of claims 1 to 3, which satisfies the following formula: νM≧1.0×10 -5 mol / cm 3

5. 5. The rubber composition for tires according to claim 1, wherein the content of the filler is 5 to 200 parts by mass per 100 parts by mass of the rubber component, and the content of the organosilicon compound is 0.1 to 20 parts by mass per 100 parts by mass of silica.

6. 6. The rubber composition for tires according to claim 1, wherein the silica content in 100% by mass of the filler is 30% by mass or more.

7. 7. The rubber composition for tires according to claim 1, wherein the content of the styrene-butadiene rubber in 100% by mass of the rubber component is 30% by mass or more.

8. 8. The rubber composition for tires according to claim 1, wherein the content of the styrene-butadiene rubber is 50 to 90% by mass, and the content of the butadiene rubber is 10 to 40% by mass, based on 100% by mass of the rubber component.

9. 9. The rubber composition for tires according to claim 1, wherein the content of the dialkyldithiophosphate compound is 0.1 to 10 parts by mass based on 100 parts by mass of the rubber component.

10. 10. The rubber composition for tires according to claim 1, wherein the content of sulfur per 100 parts by mass of the rubber component is 5.0 parts by mass or less.

11. 10. The rubber composition for tires according to claim 1, wherein the content of sulfur per 100 parts by mass of the rubber component is 1.0 part by mass or less.

12. 12. The rubber composition for tires according to claim 1, wherein the content of the plasticizer is 5 to 30 parts by mass based on 100 parts by mass of the rubber component.

13. The rubber composition for tires according to any one of claims 1 to 12, wherein the contents of silica and plasticizer per 100 parts by mass of the rubber component satisfy the following formula: 2.4≦Silica content / Plasticizer content≦4.0

14. The rubber composition for tires according to any one of claims 1 to 13, wherein the contents of silica and resin per 100 parts by mass of the rubber component satisfy the following formula: 10≦Silica content / resin content≦20

15. A tire using the rubber composition according to any one of claims 1 to 14 in its tread.

Citation Information

Patent Citations

  • Tread rubber for tire

    JP2003213044A

  • Rubber composition for tread of tire

    JP2007186567A

  • Studless tire for automobile

    JP2011032480A

  • Pneumatic tire

    JP2019210327A

  • Tread rubber composition and pneumatic tire

    JP2020041077A